Unconscious Search - A New Structured Search Algorithm for Solving Continuous Engineering Optimization Problems Based on the Theory of Psychoanalysis - Ardjmand, Ehsan; Amin-Naseri, Mohammad Reza (Advances in Swarm Intelligence, 2012)
Many metaheuristic methods are based on the ability of systems in Nature to optimize on aspects of their performance. One such system is the human brain with its capacity for optimizing towards a general state of mental balance. The Theory of Psychoanalysis propounded by Sigmund Freud is generally recognized as an account of the mechanisms involved in psychological processes. It is possible to draw an analogy between the practice of psychoanalysis and the treatment of optimization problems. The proposed new Unconscious Search (US) method shares in some features with the procedure attempted in psychoanalysis to elicit the suppressed contents of the subject’s mind. One bounded and several unbounded benchmark problems have been solved using the proposed algorithm; the results were satisfactory when compared against earlier results obtained using other known methods.